Multistate Outbreak of Salmonella Virchow Infections Linked to a Powdered Meal Replacement Product—United States, 2015–2016. (7th March 2018) - Gambino-Shirley, Kelly J; Tesfai, Adiam; Schwensohn, Colin A; Burnett, Cindy; Smith, Lori; Wagner, Jennifer M; Eikmeier, Dana; Smith, Kirk; Stone, Jolianne P; Updike, Dawn; Hines, Jonas; Shade, Lauren N; et al.
Abstract: Background: Nontyphoidal Salmonella is the leading cause of bacterial gastroenteritis in the United States. Meal replacement products containing raw and "superfood" ingredients have gained increasing popularity among consumers in recent years. In January 2016, we investigated a multistate outbreak of infections with a novel strain of Salmonella Virchow. Methods: Cases were defined using molecular subtyping procedures. Commonly reported exposures were compared with responses from healthy people interviewed in the 2006–2007 FoodNet Population Survey. Firm inspections and product traceback and testing were performed. Results: Thirty-five cases from 24 states were identified; 6 hospitalizations and no deaths were reported. Thirty-one of 33 (94%) ill people interviewed reported consuming a powdered supplement in the week before illness; of these, 30 (97%) reported consuming product A, a raw organic powdered shake product consumed as a meal replacement. Laboratory testing isolated the outbreak strain of Salmonella Virchow from leftover product A collected from ill people's homes, organic moringa leaf powder (an ingredient in product A), and finished product retained by the firm. Firm inspections at 3 facilities linked to product A production did not reveal contamination at the facilities. Traceback investigation identified that the contaminated moringa leaf powder was imported from South Africa. Conclusions: This investigation identified a novel outbreak vehicle and highlighted the potential risk with similar products not intended to be cooked by consumers before consuming. The company issued a voluntary recall of all implicated products. As this product has a long shelf life, the recall likely prevented additional illnesses. Abstract : This investigation linked a multistate outbreak of Salmonella Virchow infections to a raw powdered meal replacement product. It highlights the complex nature of food safety and potential risks with similar products not intended to be cooked by consumers before consuming.